Vitrectomy with and without scleral buckling for retinal detachment - Siqueira,Rubens Camargo (2007)
PURPOSE: To compare the surgical results of vitrectomy with and without scleral buckling for rhegmatogenous retinal detachment (RD). METHODS: Fifty-one patients with rhegmatogenous retinal detachment with proliferative vitreoretinopathy (PVR) at different stages were submitted to pars plana vitrectomy as the primary surgery, 23 patients (45.09%) with scleral buckle (group I) and 28 (54.90%) without scleral buckle (group II). Visual acuity, anterior segment complications, intraocular pressure, strabismus and retina reattachment rate were evaluated in both groups. RESULTS: The anatomical success and postoperative complications were similar in both groups. Retinal reattachment was achieved in 20 of 23 eyes (87%) of group I and in 24 of 28 eyes (85.7%) of group II after the initial surgery (p=1.000). Elevated intraocular pressure was noted in 2 eyes (8.7%) of group I and 1 eye (3.6%) of group II (p=0.583). Corneal abnormalities were seen in 3 eyes (13%) of group I and 2 eyes (7.19%) of the group II (p=0.647). Visual acuity improved from a preoperative median of 20/200 to a median of 20/100 in group 1 and from 20/400 to 20/100 in group 2; the difference between the two groups was statistically significant (p<0.05). The mean follow-up period was 10 months, ranging from 6 to 18 months. CONCLUSIONS: Both surgical procedures had similar reattachment rates. Intra- and postoperative complications were similar considering both procedures. Visual acuity improved significantly in group 2 (vitrectomy without scleral buckling).